ABU NASR FARABI'S MORAL VALUES IN MODERN EDUCATIONAL PEDAGOGY - Yuldashev, Fakhriddin (MMIT Proceedings, 2023)
In the philosophical and scientific heritage of Abu Nasr Farabi, an important place is occupied by the question of man and his essence, the inseparable connection of human life with society through mental strength and emotional and spiritual qualities. Thus, Farabi presents his most valuable views on the formation of society and personality. This article is devoted to highlighting the importance of the expression of moral values in the field of modern pedagogy in the philosophy of Farabi.